Natural elicitors, effectors and modulators of plant responses - Maffei, Massimo E; Arimura, Gen-Ichiro; Mithöfer, Axel (Natural product reports, 2012)
Covering: up to April 2012 In plants, successful defense relies on fast and specific response to biotic attack. In plant-microbial and plant-plant interactions several elicitors, effectors and modulators are recognized by specific and unspecific receptors that trigger signal cascades eventually leading to gene expression and plant responses. Here we review the chemical nature and signaling pathways of natural products released by microorganisms, herbivores, and plants during pathogenic infections, herbivory, symbioses and allelopathic interactions. This review summarizes the functional role of natural elicitors, effectors and modulators of plant responses to biotic stress.